Bisphenol A Exposure Disrupts Organelle Distribution and Functions During Mouse Oocyte Maturation - Pan, Meng-Hao; Wu, Yu-Ke; Liao, Bi-Yun; Zhang, Hui; Li, Chan; Wang, Jun-Li; Hu, Lin-Lin; Ma, Baohua (Frontiers in Cell and Developmental Biology, 2021)
Bispherol A (BPA) is one of the ubiquitous environmental endocrine disruptors (EEDs), previous studies have been shown the reproduction toxicity of BPA could cause severe effects on the mammal oocytes, and disturb the quality of mature oocytes. However, the toxic effects of BPA on the organelles of mouse oocytes have not been reported. In this study, to investigate whether BPA can be toxic to the organelles, we used different concentrations of BPA (50 μM, 100 μM, 200 μM) to culture mouse oocytes in vitro. The results showed that 100μM BPA exposure could significantly decreased the developmental capacity of oocytes. Then we used the immunofluorescence staining, confocal microscopy and western blotting to investigate the toxic effects of BPA on the organelles. The results revealed that the mitochondrial dysfunction which is manifested by abnormal distribution and decreased mitochondrial membrane potential. Moreover, the endoplasmic reticulum (ER) is abnormally distributed which is accompanied by ER stress showing with the increased expression of GRP78. For the Golgi apparatus, BPA exposure dose not disorder the Golgi apparatus distribution but caused abnormal structure of Golgi apparatus, which is manifested by the decrease of GM130 protein expression. Moreover, we also found that BPA exposure led to the damage of lysosome, which were showed by the increase of the LAMP2 protein expression. Collectively, our findings demonstrated that the exposure of BPA could damage the normal function of the organelles, which may explain the reduced maturation quality of oocytes.